Climate variability of precipitation in Ceará Region, Northeast of Brazil - da Silva, Maria Daniele Pereira Bessa (2023)
The state of Ceará is a semi-arid region located in the Northeast region of Brazil, characterized by an irregular rainy season, great climate variability mainly driven by the El Niño–Southern Oscillation (ENSO), Sea Surface Temperature (SST) of the tropical South Atlantic and extreme weather events. Droughts and their effects were studied to determine their frequency and help reduce their economic, social and environmental impacts. For that, we evaluated the space-time variability of the Standardized Precipitation Index (SPI) and characterized the drought for the twelve hydrographic regions of the State of Ceará in the scales of 3, 6 and 12 months. The data comprise the period 1980-2020 considering the monthly values of precipitation provided by the Cearense Foundation of Meteorology and Water Resources (FUNCEME). During the years 1982 and 1993, the SPI detected the greatest droughts in the state. It was also verified that 1996 and 1998 were the years with less intense dry events, presented in the 3, 6 and 12 month scales of the SPI. The index proved to be a useful tool for identifying drought in the study area at different time scales. Using wavelet analysis we found increases in spectral power at periodicities of 4-10 years, especially around 1982 and 2011, but these oscillations do not seem to be significant above the red noise spectrum. We found that cooler and warmer ENSO conditions and tropical South Atlantic SST variability were related to wetter rainy seasons, while opposite SST conditions to drier seasons.